A Assistance in Processing Kokang Leaf Pupur Dingin to Increase Product Value Added in Dasawisma Activities in Kota Bangun I Village - Miftakhur Rohmah; Nike Widuri; Yulian Andriyani (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Kokang leaves (Lepisanthes amoena) are a native Kalimantan plant that have long been used by local communities as a natural raw material for traditional skin care products in the form of pupur dingin. However, their utilization remains limited to personal or household use and has not been developed into products with higher economic value. This situation has led to the emergence of a community-based approach to increase the utilization of local resources through simple processing technologies. This community service activity aims to strengthen the capacity of Dasawisma members in Kota Bangun I Village, Kutai Kartanegara Regency, in processing kokang leaves into value-added products, and to evaluate whether such processing is economically viable at the household scale. The program was implemented using a Participatory Action Research (PAR) approach, involving participatory discussions, hands-on training, and guided production practices. Economic feasibility was assessed using the Hayami value-added method, applied to a standardized household-scale production scenario to provide a realistic estimate of value added. The findings indicate that kokang leaves can be processed into pupur dingin using simple, locally accessible technology. The participatory approach was observed to enhance participant knowledge and practical skills, as evidenced by successful product replication during guided training and active engagement in group reflections. The value-added analysis shows that the processing activity generates a positive added value of IDR 9,500 per kg of raw material, with a value-added ratio of 47.50%. This indicates that the activity is economically viable at the household level, despite its modest scale. In addition to modest economic gains, this activity demonstrates two key contributions: the technical replicability of kokang leaf processing at the household scale, and a positive though limited economic return confirmed through value-added analysis. With continued support for production consistency and simple packaging, the processing of kokang leaves into pupur dingin has the potential to be developed further as a sustainable community-based economic activity.